The National Development Plan in 2023: priorities and capacity - (:unkn) unknown (ESRI, 2024)
When the current National Development Plan (NDP) was launched in 2018, it identified a clear need for substantial public investment in Ireland and set out an ambitious programme for this investment. The needs were set out again with the launch of the renewed NDP in 2021, along with an updated set of projects. In spite of the ambition which underpinned the NDP, the latest information which informs the scale of investment needed suggests that the earlier level of ambition may have underestimated what is needed. Population growth is exceeding expectations, partly as a result of the inflow of Ukrainian refugees, and targets on greenhouse gas emissions look increasingly challenging. In the absence of any constraints, the obvious response at this point would be to increase the near-term ambition of the NDP through higher spending allocations and the acceleration of projects which are at various stages of readiness. However, the existence of capacity constraints largely in the form of labour shortages implies that the policy options which would apply in an unconstrained setting may not be optimal in the immediate future. In essence, an accelerated NDP risks generating increased inflation in the construction sector whereby the costs of delivery increase. This conflict between the need for public investment and the constraints on investment provides the context for this report, and the challenge is to provide high-level guidelines on how the conflict can be managed.
Keywords: Ireland, NDP, national development plan